Usulan Perbaikan Waktu Kerja untuk Peningkatan Kapasitas Produksi pada Perusahaan Pakan Ternak - Suparno, Adizty; Utami, Diah; Yudhistira, Gilang Awan (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
Manufacturer of cattle and goat feed, faces challenges in meeting increasing market demand. To increase production capacity, the company can implement several industrial engineering-based strategies. First, time and motion analysis can be conducted to identify and reduce non-productive activities, thereby improving work efficiency. Second, production line balancing is important to ensure equitable workload distribution, reduce waiting time between processes, and maximize output. Third, the implementation of lean manufacturing can help eliminate waste in the production process, such as overproduction and excessive waiting time. In addition, the use of automation technology in the feed processing process can accelerate production and reduce human error. The implementation of these proposed improvements is expected to significantly increase the production capacity.